2017
DOI: 10.12938/bmfh.17-010
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbial metabolite short-chain fatty acids and obesity

Abstract: Over the past decade, the gut microbiota has emerged as an essential mediator in the pathophysiology of obesity and related metabolic disorders. In this context, the reciprocal interactions of the gut microbiota structure and their metabolite profiles with host metabolism predisposing to a range of pathological conditions (e.g., insulin resistance) related to energy homeostasis have been increasingly discussed in various animal models and human cohorts. Remarkably, as the role of gut microbial metabolites as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 44 publications
(54 reference statements)
2
77
0
4
Order By: Relevance
“…Recent studies have also shown the influence of gut dysbiosis in the development and progression of atherosclerosis and subsequently CVD [76]. Furthermore, the Akkermansia muciniphila was identified to promote gut barrier functions and have attenuating effects against atherosclerosis [77]. Additionally, the human gut microbiota is associated with obesity, and some members of the gut microbiota found to be present in the feces of atherosclerotic patients, are also present in their plaques [78,79].…”
Section: Impact Of Human Gut Microbiota On Vascular Endothelimmentioning
confidence: 99%
“…Recent studies have also shown the influence of gut dysbiosis in the development and progression of atherosclerosis and subsequently CVD [76]. Furthermore, the Akkermansia muciniphila was identified to promote gut barrier functions and have attenuating effects against atherosclerosis [77]. Additionally, the human gut microbiota is associated with obesity, and some members of the gut microbiota found to be present in the feces of atherosclerotic patients, are also present in their plaques [78,79].…”
Section: Impact Of Human Gut Microbiota On Vascular Endothelimmentioning
confidence: 99%
“…Diverse microbes in the gut possess the ability to produce SCFAs. Among these, Bacteroides, Ruminococcaceae, Lachnospiraceae, Clostridia, Prevotella, Oscillospira and Verrucomicrobia ( Akkermansia muciniphila ), and Faecalibacteria are most commonly associated with the production of SCFAs 33,34,36,61,8891 . Fan et al observed that bacteroides including Blautia producta and Bacteroides thetaiotaomicron directly affect C. albicans colonization through SCFAs 2 .…”
Section: Discussionmentioning
confidence: 99%
“…SCFAs ameliorate insulin sensitivity, energy expenditure, dyslipidemia, intestinal gut‐barrier function, and inflammation, in part through initiation of G‐protein‐coupled receptor‐mediated pathways, upregulating mucin genes, and inhibiting histone deacetylases . Gut microbiota modulate body weight by changing energy balance, gut‐barrier function, inflammatory status, impaired synthesis of SCFA, and bile acid metabolism . Research studies have shown that obese individuals have an increased number of Firmicutes and Actinobacteria and decreased number of Bacteroidetes .…”
Section: Impact Of Gut Microbiota On Obesity and Inflammationmentioning
confidence: 99%